Phylogenetic and pathotype analysis of Escherichia coli swine isolates from Southern Brazil - Lilian Kolling Girardini; Franciele M. Siqueira; Carina C. Krewer; Cristina C. Krewer; Mateus M. da Costa; Agueda C. de Vargas (Pesquisa Veterinária Brasileira, 2012)
The current study evaluated the presence of virulence factors by a multiplex PCR technique and then phylogenetically classified the studied strains into groups A, B1, B2 and D, according to Clermont et al. (2000), in 152 intestinal and extraintestinal swine isolates of Escherichia coli. Seventy seven isolates tested were positive for virulence factors. Phylogenetic characterization placed 21 samples into group A, 65 into B1, 19 into B2 and 47 into D. Fourteen urine samples were classified as uropathogenic E. coli (UPEC), nine were both UPEC and enterotoxigenic E. coli (ETEC) and four were ETEC only. The most common phylogenetic classifications were B1 and D groups. Of the analyzed fecal samples, 25 were classified as ETEC. Phylogenetically, the group of higher occurrence was B1, followed by B2, A and D. For the small intestine samples, 20 were classified as ETEC. Phylogenetic analysis found groups B1 and A to be the most commons in these samples. Six isolated tissue samples were classified as ETEC and most of them were designated as group D by phylogenetic classification. The phylogenetic analysis could be employed in veterinary laboratories in the E. coli isolates screening, including the possibility of vaccine strain selection and epidemiological searches.